Hospital care utilisation patterns among the elderly at referral hospitals in Malaysia - Alkhodary, Ahmed Abdelmajed; Aljunid, Syed Mohamed; Aniza Ismail,; Nur, Amrizal Muhammad; Suzana Shahar,; Mohammad, R.; Poh, A.; Madzhar, H.; Abubakar, A. (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
The global human population is increasing, and this increase is more common among the elderly (people aged ≥60 years old and above). The elderly population is approaching 13% of the global population. Consequently, geriatric-related illnesses are expected to be more prevalent, exerting explicit pressure on healthcare systems. We explored the healthcare utilisation patterns among the elderly at public referral hospitals in Malaysia. We performed a retrospective cross-sectional study with a representative sample of elderly patients’ medical records from four referral public hospitals in Malaysia. Multiple types of data were collected from the hard-copy medical records via a structured observational checklist. A total of 434 medical records were included in the study via systematic random sampling. There were a total of 561 inpatient episodes of care. Up to 54.7% of the episodes were in the medical wards. The average length of stay was 5.8 days per episode. An average of 27.48 laboratory investigations were consumed per inpatient episode. Approximately 8.91 medications and 0.89 antibiotics were consumed per episode. Elderly patients consume a large proportion of the hospital services in Malaysia. It is recommended that the authorities should adopt health promotion and disease prevention policies that can reduce the high healthcare utilisation among elderly Malaysians.